2023
DOI: 10.3390/cells12162092
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Inflammation in Age-Related Macular Degeneration—Therapeutic Landscapes in Geographic Atrophy

Grace A. Borchert,
Hoda Shamsnajafabadi,
Monica L. Hu
et al.

Abstract: Age-related macular degeneration (AMD) is the leading cause of vision loss and visual impairment in people over 50 years of age. In the current therapeutic landscape, intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapies have been central to the management of neovascular AMD (also known as wet AMD), whereas treatments for geographic atrophy have lagged behind. Several therapeutic approaches are being developed for geographic atrophy with the goal of either slowing down disease progression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…When the cycle of retinal injury and repair continues unabated, the resident immune cells require support from the systemic immune cells in a similar manner to that reported in neurodegenerative diseases by Schwartz and Shechter in 2010 [30]. If the retinal injuries/damage become persistent such that the resident immune cells become exhausted and sustained systemic support is required, this eventually may Currently, there is no cure for early or dAMD and associated conditions; however, recently, pegcetacoplan (Syfovre) and avacincaptad pegol (Izervay) administered intravitreally were approved by the FDA for the treatment of GA [14,15]. The mainstay therapy for wAMD is anti-vascular endothelial growth factor (anti-VEGF) therapy.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…When the cycle of retinal injury and repair continues unabated, the resident immune cells require support from the systemic immune cells in a similar manner to that reported in neurodegenerative diseases by Schwartz and Shechter in 2010 [30]. If the retinal injuries/damage become persistent such that the resident immune cells become exhausted and sustained systemic support is required, this eventually may Currently, there is no cure for early or dAMD and associated conditions; however, recently, pegcetacoplan (Syfovre) and avacincaptad pegol (Izervay) administered intravitreally were approved by the FDA for the treatment of GA [14,15]. The mainstay therapy for wAMD is anti-vascular endothelial growth factor (anti-VEGF) therapy.…”
Section: Introductionmentioning
confidence: 75%
“…Life 2023, 13,2236 2 of 12 metabolic waste/deposits, and death of PR and RPE, which can progress to chronic disease states such as wAMD, geographic atrophy (GA), or subretinal fibrosis [4][5][6][7][8][9][10][11][12][13]. Currently, there is no cure for early or dAMD and associated conditions; however, recently, pegcetacoplan (Syfovre) and avacincaptad pegol (Izervay) administered intravitreally were approved by the FDA for the treatment of GA [14,15]. The mainstay therapy for wAMD is anti-vascular endothelial growth factor (anti-VEGF) therapy.…”
Section: Introductionmentioning
confidence: 99%
“…An excess of ROS can adversely affect complement functionality in various ways [315]. Chen et al demonstrated in cultured RPE cells from mouse or human donors that the phagocytosis of oxidized POS by RPE cells downregulates the synthesis of CFH in RPE [316].…”
Section: Reactive Oxygen Species Excess and Complement Anomaliesmentioning
confidence: 99%
“…Novel therapeutic techniques such as gene therapy using recombinant adeno-associated virus vectors delivering VEGF-inhibitory compounds and subsequent expression for long-term nAMD control are emerging [180,181] . However a staggering percentage of nAMD patients stabilized by anti-VEGF treatment still go onto to develop MA: more than 98 percent at 7 years in some studies [182] .New treatments for GA in dry AMD include complement pathway C3 and C5 inhbitors [183][184][185][186] .In all of these efforts, the ability to uitilize advances in imaging modalities to detect and document disease findings remains a critical stepping stone to future therapies.…”
Section: Ongoing Trends In Management and Researchmentioning
confidence: 99%